Human papillomavirus oropharynx carcinoma: Aggressive de‐escalation of adjuvant therapy. Issue 1 (23rd September 2020) - Moore, Eric J.; Van Abel, Kathryn M.; Routman, David M.; Lohse, Christine M.; Price, Katharine A. R.; Neben‐Wittich, Michelle; Chintakuntlawar, Ashish V.; Price, Daniel L.; Kasperbauer, Jan L.; Garcia, Joaquin J.; Hinni, Michael L.; Patel, Samir H.; et al.
Abstract: Background: Aggressive dose de‐escalated adjuvant radiation therapy (RT) in patients with human papillomavirus–associated oropharyngeal squamous cell carcinoma (HPV(+)OPSCC). Methods: Patients with HPV(+)OPSCC on a phase II clinical trial of primary surgery and neck dissection followed by dose de‐escalated RT (N = 79) were compared with a cohort of patients who received standard adjuvant therapy (N = 115). Local recurrence‐free, regional recurrence‐free, distant metastases‐free survival, and progression‐free survival (PFS) were assessed. Results: Of 194 patients, 23 experienced progression at a median of 1.1 years following surgery (interquartile range [IQR] 0.7‐2.0; range 0.3‐5.4); 10 patients in the de‐escalated cohort and 13 patients in the standard cohort. The 3‐year PFS rate for the de‐escalated cohort was 87%, and in the standard cohort was 90% (hazard ratio [HR] 1.18, 95% confidence interval (CI) [0.50‐2.75]). Conclusion: Patients with HPV(+)OPSCC who undergo surgical resection and neck dissection and meet criteria for adjuvant therapy can undergo aggressive dose de‐escalation of RT without increasing risk of progression locally, regionally or at distant sites.